VISIBILITAS DAN PENETAPAN HARGA TERHADAP PENGALAMAN PELANGGAN AYAM GEPREK SA’I CABANG BEJI - Feby Karunia Putri; Sumartik Sumartik; Misti Hariasih (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
In this era of rapid technological advancement, humans are constantly seeking and choosing various ways to do things quickly and easily, including when it comes to dining. Fast food restaurants have become common in many cities. The food industry in Indonesia is currently experiencing rapid development. Therefore, intense competition arises to create and fulfill the increasingly sophisticated and high demands of consumers. This study aims to analyze the impact of visibility and pricing on customer experience. The research utilizes a quantitative method, with a research design involving hypothesis testing. In this study, data is obtained from two sources, namely primary data and secondary data. An online questionnaire is distributed to customers of Beji Geprek Sa'i Fast Food Restaurant, Beji Branch, as research subjects to collect primary data. Data analysis will be conducted using SPSS software, with the research sample consisting of individuals who have visited Beji Geprek Sa'i Fast Food Restaurant, Beji Branch, more than once. The questionnaire will be distributed through Google Form. Based on the conducted research, it can be concluded that the factors of visibility and pricing contribute to or influence customer experience (Y). Keywords: Visibility, Pricing, Customer Experience.